Phase 2 of the 2005 Commencement ceremony for the School of Medicine in the Gantcher Center. Photo 006 - Tobin, Joanie (Tufts Archival Research Center, 2008)
Phase 2 of the 2005 Commencement ceremony for the School of Medicine in the Gantcher Center.